(untitled) (Research, Society and Development, 2021)
The umbu tree, a plant belonging to the Spondias genus and Anacardiaceae family, has 18 species that are located in the Americas, Asia and Oceania. The fruit has been highlighted in the national and international market for its variety of bioactive compounds, which have nutraceutical and therapeutic effects. However, a better use can be obtained through the knowledge of the genetic variability of these fruits. Therefore, the objective was to carry out a review regarding the bioactive and chemical composition as well as the antioxidant activity of umbu fruits in relation to the variation of these parameters between different fruit genotypes. Despite the good physicochemical, nutritional, sensory, nutraceutical and therapeutic properties, the umbuzeiro fruits are marketed limited to the places where they are produced due to the seasonal period, for this reason, to know the specific characteristics and properties of each genotype of the fruits of the umbuzeiro is extremely important, since, knowing these properties, it is possible to point out different forms of processing, improvements in cultivation techniques, harvesting, processing and processing and increased productivity, among others.